ANALISA HUKUM KETENAGAKERJAAN TERHADAP ASAS KEADILAN PADA UNDANG-UNDANG STANDAR BURUH YANG ADIL (FAIR LABOR STANDAR ACT) TAHUN 1938 - Urip Giyono (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2017)
The cultivation of the principle of balance of interests in the rule of law that contains the value of honesty, fairness, justice, and moral demands, such as rights, obligations and responsibilities in the relationship between human beings in accordance with the principles of Pancasila, where workers and employers have a reciprocal relationship valued humanity, there is no discrimination, and seeking adjustment of understanding through deliberations. In establishing partnerships in working relationships between workers and employers, and through building partnerships the parties maintain the working conditions conductively, with due regard to the welfare of workers and their families, on the contrary the workers perform the obligations according to applicable rules and can adapt to the work environment. This in turn will create a partnership building. This harmony is a manifestation, that entrepreneurs and workers must accept and believe all that is Allah's trust to be utilized for the benefit of man Keywords : rights, duty, partnership